The Evolution of Device-Assisted Enteroscopy: From Sonde Enteroscopy to Motorized Spiral Enteroscopy - Nehme, Fredy; Goyal, Hemant; Perisetti, Abhilash; Tharian, Benjamin; Sharma, Neil; Tham, Tony C.; Chhabra, Rajiv (Frontiers in Medicine, 2021)
The introduction of capsule endoscopy in 2001 opened the last “black box” of the gastrointestinal tract enabling complete visualization of the small bowel. Since then, numerous new developments in the field of deep enteroscopy have emerged expanding the diagnostic and therapeutic armamentarium against small bowel diseases. The ability to achieve total enteroscopy and visualize the entire small bowel remains the holy grail in enteroscopy. Our journey in the small bowel started historically with sonde type enteroscopy and ropeway enteroscopy. Currently, double-balloon enteroscopy, single-balloon enteroscopy, and spiral enteroscopy are available in clinical practice. Recently, a novel motorized enteroscope has been described with the potential to shorten procedure time and allow for total enteroscopy in one session. In this review, we will present an overview of the currently available techniques, indications, diagnostic yield, and complications of device-assisted enteroscopy.